‘A World Where Many Worlds Fit’: On the Zapatista Model of a Just Society - Luis Gomez Romero (Law Text Culture, 2023)
On January 1st, 1994, the Indigenous Zapatista Army of National Liberation (EZLN, Ejército Zapatista de Liberación Nacional) rose up in arms, in the south-eastern Mexican state of Chiapas, in response to the daily oppressions and injustices Indigenous peoples face within Mexican neo-colonial political systems and juridical orders. The Zapatista movement is grounded on a distinct methodology that structures political thought in the framework of Maya worldviews. This resulted in a unique political practice in which, for example, revolution does not aim to seize power, but rather to transform civil society. This article discusses the key political principles informing the Zapatista model of a just society that results from such a methodology and practices: the centuries-old Indigenous moral economy that resists turning land into a commodity, the radicalization of democracy through the mandate of command by obeying (mandar obedeciendo), and the transformation of pluralism into the pursuit of a world where other worlds fit (un mundo donde quepan otros mundos).